Phenomena of Juvenile Deliquency (Sociological Study on The Case Assisted by UPTD PPA Makassar City) - Sopian Tamrin; Idham Irwansyah; Rafli Rafli (Universitas of Muhammadiyah Makassar, 2023)
Cases of children dealing with the law in Makassar City will increase to 35% in 2022. Through this research, it is necessary to determine the factors that underlie children committing law violations at UPTD PPA Makassar City. Qualitative is used as an approach and case studies as its type. Data were collected through observation and interviews as well as documentation activities. Data were analyzed by reduction, presentation, and conclusion. Research informants consisted of ABH, ABH families, and UPTD PPA managers. This study found that the factors underlying children dealing with the law include: (1) Family conditions, unstable family conditions, frequent fights, broken homes, lack of support, and experiences of domestic violence (2) Psychology of the social environment; a social environment that tends to deviate, associates, and the urge to imitate. (3) Socio-economic disparities, basically the children in the case are those from underprivileged families. Their actions are also based on meeting their needs.